Elevated expression of myosin X in tumours contributes to breast cancer aggressiveness and metastasis - Cao, R (Nature Publishing Group, 2014)
BACKGROUND: Myosin X (MYO10) was recently reported to promote tumour invasion by transporting integrins to filopodial tips in breast cancer. However, the role of MYO10 in tumours remains poorly defined. Here, we report that MYO10 is required in invadopodia to mediate invasive growth and extracellular matrix degradation, which depends on the binding of MYO10's pleckstrin homology domain to PtdIns(3,4,5)P3. METHODS: The expression of MYO10 and its associations with clinicopathological and biological factors were examined in breast cancer cells and breast cancer specimens (n=120). Cell migration and invasion were investigated after the silencing of MYO10. The ability of cells to form invadopodia was studied using a fluorescein isothiocyanate-conjugated gelatin degradation assay. A mouse model was established to study tumour invasive growth and metastasis in vivo. RESULTS: Elevated MYO10 levels were correlated with oestrogen receptor status, progesterone receptor status, poor differentiation, and lymph node metastasis. Silencing MYO10 reduced cell migration and invasion. Invadopodia were responsible for MYO10's role in promoting invasion. Furthermore, decreased invasive growth and lung metastasis were observed in the MYO10-silenced nude mouse model. CONCLUSIONS: Our findings suggest that elevated MYO10 expression increases the aggressiveness of breast cancer; this effect is dependent on the involvement of MYO10 in invadopodial formation.